2019
DOI: 10.1111/vsu.13360
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after surgical and conservative treatments of canine peritoneopericardial diaphragmatic hernia: A multi‐institutional study of 128 dogs

Abstract: ObjectiveTo compare demographics and disease characteristics in dogs in which peritoneopericardial diaphragmatic hernia (PPDH) had been diagnosed and report outcomes after surgical treatment (ST) or conservative treatment (CT).Study designRetrospective study.Sample populationOne hundred twenty‐eight dogs (91 ST, 37 CT) in which PPDH had been diagnosed.MethodsMedical records were reviewed for demographics, perioperative findings, and outcomes. Follow‐up was obtained via telephone interview and email corresponde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 14 publications
0
33
0
5
Order By: Relevance
“…Based on the histopathology results and perfusion of the herniated liver on CT, the hepatic parenchyma incarcerated in a PPDH showed chronic liver changes, although the patient had no symptoms and abnormal blood work results. In a retrospective study of dogs with PPDH, histopathologic results of the herniated liver with grossly abnormal appearance were also hepatic or portal fibrosis [ 11 ]. To our knowledge, there are no imaging studies of altered perfusion in incarcerated liver in a PPDH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the histopathology results and perfusion of the herniated liver on CT, the hepatic parenchyma incarcerated in a PPDH showed chronic liver changes, although the patient had no symptoms and abnormal blood work results. In a retrospective study of dogs with PPDH, histopathologic results of the herniated liver with grossly abnormal appearance were also hepatic or portal fibrosis [ 11 ]. To our knowledge, there are no imaging studies of altered perfusion in incarcerated liver in a PPDH.…”
Section: Discussionmentioning
confidence: 99%
“…Large defects in the diaphragm can result in adhesions of abdominal organs to the pericardium and incarcerate of organs in the pericardium [ 12 ]. Dogs that received surgical treatment tended to show clinical signs associated with PPDH, and the herniation of liver was confirmed in 66% of them [ 11 ]. It has also been reported that herniation of the liver is associated with a poor prognosis in fetal congenital diaphragmatic hernia in human medicine, suggesting compression of the lung by the herniated liver, and increased size of defect in the diaphragm and disturbed regulation of liver growth [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are three classifications of the pentalogy of Cantrell. In class 1, patients have all five defects, patients with class 2 have four defects, including intracardiac and ventral wall anomalies, and patients with class 3, also known as the incomplete expression, have various combinations of abnormalities including a sternal defect ( 4 , 5 ). To date, in veterinary medicine, this classification does not exist.…”
Section: Discussionmentioning
confidence: 99%
“…Animals with PPDH often have other concurrent congenital abnormalities such as midline defects (e.g., umbilical hernia, cleft palate, sternal abnormalities) and cardiac defects (e.g., ventricular septal defects, subaortic stenosis, pulmonic stenosis, atrial septal defect) (4)(5)(6)(7)(8). Peritoneopericardial diaphragmatic hernia is commonly seen as a congenital abnormality in several animals of the same litter (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…2,[4][5][6][7] Theoretically all visceral organs may be displaced, but liver, gall bladder and small intestines are most commonly herniated. 2,5,7 Physical examination may reveal muffled heart sounds, heart murmurs or decreased lung sounds, thoracic borborygmi or an empty abdomen on palpation. [2][3][4]6,7 Affected animals are asymptomatic or show non-specific clinical signs like lethargy, weight loss, anorexia, exercise intolerance, gastrointestinal or respiratory clinical signs or even cardiovascular collapse.…”
Section: Introductionmentioning
confidence: 99%